2018
DOI: 10.1117/1.oe.57.6.061605
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reflection screens fabricated by holographic wavefront printer

Abstract: Abstract. Several wavefront printers have been recently proposed. Since the printers can record an arbitrary computer-generated wavefront, they are expected to be useful for fabricating complex mirror arrays used in front projection 3-D screens without using real existing optics. We prototyped two transparent reflective screens using our hologram printer in experiments. These screens could compensate for a spherically distorted reference wave caused by a short projection distance to obtain an ideal reference w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Seeking ferromagnetic semiconductors with a high Curie temperature and inorganic luminescent materials (phosphors) with a short lifetime is a great challenge in semiconductor spintronics and projection television screen applications. Bifunctional materials, especially those with both photoluminescence (PL) and magnetism, are widely used in multifunctional devices and biological diagnosis and treatment due to their unique and superior properties. At present, the optical/magnetic bifunctional materials reported in the literature are mainly composite materials, such as coating materials, mosaic materials, and so on. , Zhang et al reported the hollow Fe 3 O 4 @SiO 2 @α-NaYF 4 /Yb, Er composite, which can emit visible light under the excitation of near-infrared and has the effect of magnetic targeting under the action of an external magnetic field . Abbas et al found that NaYF 4 :Yb, Er@Fe x O y modified the surface of the shell by a dopamine molecule, which makes the composite nanoparticles more water-soluble and less toxic .…”
Section: Introductionmentioning
confidence: 99%
“…Seeking ferromagnetic semiconductors with a high Curie temperature and inorganic luminescent materials (phosphors) with a short lifetime is a great challenge in semiconductor spintronics and projection television screen applications. Bifunctional materials, especially those with both photoluminescence (PL) and magnetism, are widely used in multifunctional devices and biological diagnosis and treatment due to their unique and superior properties. At present, the optical/magnetic bifunctional materials reported in the literature are mainly composite materials, such as coating materials, mosaic materials, and so on. , Zhang et al reported the hollow Fe 3 O 4 @SiO 2 @α-NaYF 4 /Yb, Er composite, which can emit visible light under the excitation of near-infrared and has the effect of magnetic targeting under the action of an external magnetic field . Abbas et al found that NaYF 4 :Yb, Er@Fe x O y modified the surface of the shell by a dopamine molecule, which makes the composite nanoparticles more water-soluble and less toxic .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, research is being done to create see-through light field displays that are suitable for augmented reality applications. One popular approach for this kind of displays is to project an integral image on a holographic optical element that resembles a microlens or micromirror array [6][7][8][9]. In order to produce sharp and correct 3D images, these setups require an accurate calibration of the projector with relation to the screen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 3D displays, including holography display [3][4][5], integral imaging display [6][7][8][9], volumetric display [10,11] and so on, have received extensive attention. Integral imaging is considered to be one of the most promising display technologies.…”
Section: Introductionmentioning
confidence: 99%